THE MORPHOLOGICAL PROPERTIES OF CERTAIN DENTAL POWDERS FOR AIR-ABRASIVE (AIR-BLASTING) PROCEDURES - Golinka, Olga; Karpchuk, Liudmyla; Mochalov, Iurii; Maryan-Yovbak, Viktoria; Kulish, Andrii; Sikura, Antonina (Eastern Ukrainian Medical Journal, 2024)
The objectives of the study was to study the particle sizes, morphological properties and their structural distribution in the composition of some dental powders for air-abrasive (air-blasting) procedures. Materials and methods. The next powders were investigated: "Clinpro Glycine Prophy Powder" ("3M ESPE", USA-Germany), a universal for supra- and subgingival procedures; "BP CC-03 AIR‑FLOW (glycine)" ("Ezmedix", Ukraine); "Perlyna P" Erythritol, 14 μm" ("MDS", Ukraine) for subgingival use; "Perlyna" Erythritol, ≥24 μm" ("MDS", Ukraine) for supragingival use; "Perlyna+" Glycine ≥24 μm" ("MDS", Ukraine) for supragingival use. Light microscopy was performed at different magnifications and lighting, and with the help of a standard Goryaev’s two-grid camera (hemocytometer). An automatic laser liquid particle analyzer was used for the granulometry of the investigated powders, the working medium was isopropanol. Results. Light microscopy of samples of dental powders for air-abrasive procedures showed their different microstructures, which differed to a large extent. "Clinpro Glycine Prophy Powder" was mostly homogeneous in size, in color and clarity, mostly free of sharp edges and corners, with a particle size of mostly up to 50 µm. In "BP CC-03 AIR-FLOW (Glycine)" the particle sizes were uneven with some "giant size" particles that had more sharp edges and exceeded 50 μm and 200 μm of size. The particles of the powder "Perlyna P" Erythritol, 14 μm" for subgingival use were less heterogeneous in size, mostly irregular in shape with a tendency to form prismatic and tetrahedral structures, with sharp edges. A significant number was with a size of 50 microns. In the powder "Perlyna" Erythritol, ≥24 μm" for supragingival use, more large crystals were visually determined, there was a greater contrast in size. Powder "Perlyna+" Glycine ≥24 μm for supragingival use distinguished by a larger particle size, with a fraction of small fragments (there is a marked contrast in size, the particles resembled ground sugar, with sharp edges and faces). Laser liquid granulometry showed that “Clinpro Glycine Prophy Powder” was dominated by the size fraction from 18.97 to 40.15 μm; "BP CC-03 AIR-FLOW (glycine)" – from 17.05 to 117.10 microns; in the powder "Perlyna P" Erythritol, 14 μm" for subgingival use – from 26.16 to 76.33 μm; in the powder "Perlyna" Erythritol, ≥24 μm" for supragingival use – from 44.69 to 130.30 μm; in the powder "Perlyna+" Glycine ≥24 μm" for supragingival use – from 53.36 to 145.10 μm. Conclusions: Therefore, light microscopy and laser liquid granulometry of some powders for professional oral hygiene from different manufacturers showed that they did not have a rounded shape (which is recognized as the least aggressive when interacting with tissues in the oral cavity). All powders had a contrast in particle sizes and mainly irregular particle shapes, the vast majority of them were polygonal and had sharp faces and edges. Most of the powders, in which the specified particle sizes were declared, had significant deviations according to this indicator. Thus, it is possible to express the opinion that the vast majority of powders for air-abrasive processing in the oral cavity available on the dental market of Ukraine require further research and improvement The objectives of the study was to study the particle sizes, morphological properties and their structural distribution in the composition of some dental powders for air-abrasive (air-blasting) procedures. Materials and methods. The next powders were investigated: "Clinpro Glycine Prophy Powder" ("3M ESPE", USA-Germany), a universal for supra- and subgingival procedures; "BP CC-03 AIR‑FLOW (glycine)" ("Ezmedix", Ukraine); "Perlyna P" Erythritol, 14 μm" ("MDS", Ukraine) for subgingival use; "Perlyna" Erythritol, ≥24 μm" ("MDS", Ukraine) for supragingival use; "Perlyna+" Glycine ≥24 μm" ("MDS", Ukraine) for supragingival use. Light microscopy was performed at different magnifications and lighting, and with the help of a standard Goryaev’s two-grid camera (hemocytometer). An automatic laser liquid particle analyzer was used for the granulometry of the investigated powders, the working medium was isopropanol. Results. Light microscopy of samples of dental powders for air-abrasive procedures showed their different microstructures, which differed to a large extent. "Clinpro Glycine Prophy Powder" was mostly homogeneous in size, in color and clarity, mostly free of sharp edges and corners, with a particle size of mostly up to 50 µm. In "BP CC-03 AIR-FLOW (Glycine)" the particle sizes were uneven with some "giant size" particles that had more sharp edges and exceeded 50 μm and 200 μm of size. The particles of the powder "Perlyna P" Erythritol, 14 μm" for subgingival use were less heterogeneous in size, mostly irregular in shape with a tendency to form prismatic and tetrahedral structures, with sharp edges. A significant number was with a size of 50 microns. In the powder "Perlyna" Erythritol, ≥24 μm" for supragingival use, more large crystals were visually determined, there was a greater contrast in size. Powder "Perlyna+" Glycine ≥24 μm for supragingival use distinguished by a larger particle size, with a fraction of small fragments (there is a marked contrast in size, the particles resembled ground sugar, with sharp edges and faces). Laser liquid granulometry showed that “Clinpro Glycine Prophy Powder” was dominated by the size fraction from 18.97 to 40.15 μm; "BP CC-03 AIR-FLOW (glycine)" – from 17.05 to 117.10 microns; in the powder "Perlyna P" Erythritol, 14 μm" for subgingival use – from 26.16 to 76.33 μm; in the powder "Perlyna" Erythritol, ≥24 μm" for supragingival use – from 44.69 to 130.30 μm; in the powder "Perlyna+" Glycine ≥24 μm" for supragingival use – from 53.36 to 145.10 μm. Conclusions: Therefore, light microscopy and laser liquid granulometry of some powders for professional oral hygiene from different manufacturers showed that they did not have a rounded shape (which is recognized as the least aggressive when interacting with tissues in the oral cavity). All powders had a contrast in particle sizes and mainly irregular particle shapes, the vast majority of them were polygonal and had sharp faces and edges. Most of the powders, in which the specified particle sizes were declared, had significant deviations according to this indicator. Thus, it is possible to express the opinion that the vast majority of powders for air-abrasive processing in the oral cavity available on the dental market of Ukraine require further research and improvement.